Implementasi Aplikasi Administrasi Paguyuban UMKM Taman Harapan Baru (THB) Kota Bekasi - Sutisna; Magfiratul Jannah; Lukmanul Hakim; Pania Putra Nurkholif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This Community Service activity aims to implement administrative applications that can help Micro, Small and Medium Enterprises (MSMEs) actors in the Taman Harapan Baru Association (THB) Bekasi City. MSMEs are an important part of the Indonesian economy and have a significant contribution to the country's GDP. In the era of the industrial revolution 4.0, application technology trends that focus on data exchange and automation have great potential in the development of MSMEs. However, there are still many MSMEs in Indonesia who do not have a structured administration system and well-organized filing. Therefore, this service activity uses a descriptive analytical method to find out what kind of information system is expected by MSME actors and can help them manage their business administration. Based on this method, it was found that SMEs expect an information system that is automated, simple, and easy to understand to assist them in managing their business administration. In this service activity, administrative applications will be implemented that are tailored to the needs and expectations of MSME actors in the THB Association. Through collaboration with MSME actors, it is hoped that this application can help improve the efficiency and effectiveness of their business administration, as well as assist them in achieving business growth and sustainability.